Evaluasi Tindakan Aseptis Tenaga Teknis Kefarmasian pada Proses Rekonstitusi dan Penyimpanan Injeksi Antibiotik di Ruang Rawat Inap RS UNS - Rahma Noviyanti, Eka; Murtisiwi, Lusia (Jurnal Farmasi (Journal of Pharmacy), 2022)
This study aims to evaluate the application of aseptic measures by Pharmaceutical Technical Personnel (TTK) during reconstitution and storage of antibiotics, including personal protective equipment (PPE), room and equipment, mixing process, and storage of antibiotic injections in the inpatient unit of UNS Hospital. This research is a non-experimental research with a descriptive design. Data collection was carried out by direct observation to health workers who carried out reconstitution and storage of antibiotic injections in the inpatient unit of UNS Hospital. The research sample was 49 respondents. The analysis in this study was carried out quantitatively by calculating the percentage of compliance with the Standard Operating Procedure (SOP) at the UNS Hospital Inpatient and then presented descriptively. The results showed that the process of reconstitution and storage of antibiotic injections in the inpatient installation of UNS Hospital was in accordance with the percentage of conformity of preparation procedures of 89%, mixing procedures of 82%, storage procedures of 90%, distribution procedures of 76%.